Intraductal papillary mucinous carcinoma versus pancreatic ductal adenocarcinoma: A systematic review and meta-analysis. (November 2019) - Aronsson, Linus; Bengtsson, Axel; Torén, William; Andersson, Roland; Ansari, Daniel
Abstract: Background: Previous studies have indicated that there may be a difference in tumor biology between intraductal papillary mucinous carcinoma (IPMC) and pancreatic ductal adenocarcinoma (PDAC). However, the data are still controversial. The aim of this systematic review and meta-analysis was to summarize and compare the outcome of IPMC and PDAC after surgical resection. Methods: Studies comparing IPMC and PDAC were identified using Medline and Embase search engines. Primary outcomes of interest were survival and recurrence. Secondary outcomes were clinicopathological characteristics. Meta-analysis of data was conducted using a random-effects model. Results: A total of 14 studies were included. Pooled analysis revealed an improved 5-year overall survival (OS) for IPMC compared to PDAC (OR 0.23, 95% CI 0.09–0.56). Both colloid and tubular IPMC showed improved 5-year OS compared to PDAC (OR 0.12, 95% CI 0.05–0.25 and OR 0.38, 95% CI 0.26–0.54, respectively). Median survival time ranged from 21 to 58 months in the IPMC group compared to 12–23 months in the PDAC group. No meta-analysis could be performed on recurrence or on time-to-event data. Descriptive data showed no survival difference for higher TNM stages. IPMC was more often found at a TNM-stage of 1 (OR 4.40, 95% CI 2.71–7.15) and had lower rates of lymph node spread (OR 0.43, 95% CI 0.32–0.57). Conclusion: Available data suggest that IPMC has a more indolent course with a better 5-year OS compared to PDAC. The histopathological features are less aggressive in IPMC. The reason may be earlier detection. However, for IPMC with higher TNM stages the survival seems to be similar to that of PDAC. Highlights: IPMC has a more indolent course than PDAC with improved 5-year OS. The histopathological features are less aggressive in IPMC. For IPMC with higher TNM stages the survival seems to be similar to that of PDAC.